Investigation of nonlinearity of photorefractive effect in LiNbO3 - Turek, Ivan; Tarjanyi, Norbert (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, the nonlinearities resulting from the simple band transport model of photorefractivity are compared with dependences experimentally obtained in LiNbO3:Fe crystals. The investigation of nonlinearities is performed for both periodic and aperiodic optical fields. The comparison shows that the space-charge field cannot be the main cause of light-induced refractive index changes.
Optica Applicata, Vol. 39, 2009, nr 3, s. 587-599
Keywords: optyka; photorefractive effect; lithium niobate